A corpus-based translation study on english-persian verb phrase ellipsis - Shahabi, Mitra (2012)
Dissertação de mest., Natural Language Processing & Human Language Technology, Faculdade de Ciências Humanas e Sociais, Univ. do Algarve, 2011